Kajian Bentuk serta Fungsi Bangunan Tradisional Rumah Adat (UMA) Masyarakat Mentawai - P.P.S, lfonsus Rifalrik; Sandra, Yofita (YASIN, 2023)
West Sumatra is one of the provinces in Indonesia which has a population not only from the Minangkabau (Malay) ethnicity. But also from ethnic groups such as the Mentawai tribe who live in the Mentawai Islands. Minangkabau is synonymous with Islam, while the Mentawai people are predominantly Christian. Likewise, the Minangkabau traditional house is called Rumah Gadang, while the Mentawai traditional house is called Uma. The division of forms in the traditional Mentawai house is generally divided into three parts. Namely the large Uma that extends, the front, middle and back. The front is called talaibo which serves to welcome guests. The central part of Uma is an area which is divided into three equal parts and functions as a party or traditional ritual. Then the last part, behind Uma there is a kitchen and it is called batsapo. Uma functions as a place for association or deliberation within one tribe to carry out all activities, be it traditional rituals or parties that are carried out within one tribe. Uma also has a goal as a medium to strengthen ties within one tribe in building good cooperation. Uma also has ornaments or decorations in the form of nature such as leaves, plants and animals, each decoration has a placement and has a special meaning, such as monkey skulls, pig skulls, turtle shells and other decorations. Qualitative Descriptive Research Methods because in my opinion this method is very suitable for my research plan because it is one of the methods that are field in nature such as interviews, questionnaires and questionnaires.